A política nacional de assistência técnica e extensão rural no assentamento Antonio Conselheiro, MT: realidade ou ficção? - Silva, José Jaconias da (2011)
This paper has as objective to understand how the National Policy of Technical Assistance and Rural Extension (PNATE) comes to the farmers of the family farming. This policy was prepared in 2004 and was celebrated by the support sectors to the family farming, because it meant a disruption with the previous extensionist model, which enjoyed the land concentration on one side, and the producing inputs companies for agriculture on the other, with several damages to the family farming. In this paper, we adopt the case study methodology, in which we observed the Empresa Matogrossense de Pesquisa Assistência Técnica e Extensão Rural (EMPAER) and farmers from the settlement Antonio Conselheiro. 187 questionnaires were applied to the settlers, as a sample of the universe. The research concludes that, if from one hand, the policy advances in favor of the family farming, on the other hand it is far from the goal of making the family farming a dynamic component of household food production chain.